The role of gut microbiota in a generalist, golden snub-nosed monkey, adaptation to geographical diet change - Yuhang Li; Yujie Yan; Haojie Wu; Yiyi Men; Yi Yang; Hengguang Fu; Derek Dunn; Xiaowei Wang; Genggeng Gao; Peng Zhang; Guixin Dong; Liyuan Hao; et al. (Animal Microbiome)
Abstract Changes in diet causing ecological stress pose a significant challenge to animal survival. In response, the gut microbiota, a crucial part of the host’s digestive system, exhibits patterns of change reflective of alterations in the host’s food component. The impact of temporal dietary shifts on gut microbiota has been elucidated through multidimensional modeling of both food component and macronutrient intake. However, the broad distribution of wild generalist and the intricate complexity of their food component hinder our capacity to ascertain the degree to which their gut microbiota assist in adapting to spatial dietary variations. We examined variation in patterns of the gut microbial community according to changes in diet and in a colobine monkey with a regional variable diet, the golden snub-nosed monkey (Rhinopithecus roxellana). Specifically, we analyse the interactions between variation in food component, macronutrient intake and the gut microbial community. We compared monkeys from four populations by quantifying food component and macronutrient intake, and by sequencing 16S rRNA and the microbial macro-genomes from the faecal samples of 44 individuals. We found significant differences in the diets and gut microbial compositions, in nutrient space and macronutrient intake among some populations. Variations in gut microbiota composition across distinct populations mirror the disparities in macronutrient intake, with a notable emphasis on carbohydrate. Geographical differences in the diet among of golden snub-nosed monkey populations will result in macronutrient intake variation, with corresponding differences in macronutrient intake driving regional differences in the compositions and abundances of gut microbiota. Importantly, the gut microbiota associated with core digestive functions does not vary, with the non-core gut microbiota fluctuating in response to variation in macronutrient intake. This characteristic may enable species heavily reliant on gut microbiota for digestion to adapt to diet changes. Our results further the understanding of the roles gut microbiota play in the formation of host dietary niches.